2002
DOI: 10.1007/s00122-001-0807-y
|View full text |Cite
|
Sign up to set email alerts
|

Different maternal origins of Japanese lowland and upland rice populations

Abstract: Plastid subtype ID (PS-ID) sequences were determined from sequence data based on CA repeats between genes rpl16 and rpl14 in Japanese lowland and upland cultivars. The PS-ID sequences of Japanese rice cultivars showed that there are different maternal origins between lowland and upland cultivars. One subtype, 6C7A, of PS-ID sequences was predominant in all but one Japanese lowland cultivar and carried a combination of the indica-specific subtype 8C8A and japonica-specific nuclear markers for the isozyme genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In the previous paper (Ishikawa et al 2002a), we reported heterozygotes in Laos where primitive cultivars were cocultivated in single fields. Also strains intermediate between indica and japonica could be seen.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the previous paper (Ishikawa et al 2002a), we reported heterozygotes in Laos where primitive cultivars were cocultivated in single fields. Also strains intermediate between indica and japonica could be seen.…”
Section: Discussionmentioning
confidence: 95%
“…The two types reveal distinct characters in all traits except for cultivated traits. In general, they are cultivated in separate fields, though on the Himalayan foot hills and South-Asian mountain areas they are cultivated in closely located fields (Sano and Morishima 1992;Ishikawa et al 2002a). In these areas, heterozygotes and intermediate types on isozyme analysis were frequently found.…”
Section: Introductionmentioning
confidence: 98%
“…Such cytoplasm-substituted cultivars are unusual. Our previous report (Ishikawa et al 2001) showed only one out of 50 lowland and 80 upland cultivars in Japan revealed such a substitution. As to the nuclear genotypes of the Japanese indica cultivars, all but one were characterized as Pgd1 3 , with a red pericarp, a slender hull, and a short apiculus hair length.…”
Section: Discussionmentioning
confidence: 99%
“…How are such cytoplasm-substituted cultivars created in nature? In upland fields, we can still see heterozygotes and extremely wide variation for morphological and physiological markers in single fields of Laos (Ishikawa et al 2001). The cultivation system adopted in primitive upland fields enables rice plants to outcross.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation